Cardiorespiratory Fitness and Gray Matter Volume in the Temporal, Frontal, and Cerebellar Regions in the General Population - Wittfeld, Katharina; Jochem, Carmen; Dörr, Marcus; Schminke, Ulf; Gläser, Sven; Bahls, Martin; Markus, Marcello R.P.; Felix, Stephan B.; Leitzmann, Michael F.; Ewert, Ralf; Bülow, Robin; Völzke, Henry; et al. (Mayo Clinic proceedings, 2020)
To analyze the association between cardiorespiratory fitness (CRF) and global and local brain volumes. We studied 2103 adults (21-84 years old) from 2 independent population-based cohorts (Study of Health in Pomerania, examinations from June 25, 2008, through September 30, 2012). Cardiorespiratory fitness was measured using peak oxygen uptake (VO2peak), oxygen uptake at the anaerobic threshold (VO2@AT), and maximal power output from cardiopulmonary exercise testing on a bicycle ergometer. Magnetic resonance imaging brain data were analyzed by voxel-based morphometry using regression models with adjustment for age, sex, education, smoking, body weight, systolic blood pressure, glycated hemoglobin level, and intracranial volume. Volumetric analyses revealed associations of CRF with gray matter (GM) volume and total brain volume. After multivariable adjustment, a 1–standard deviation increase in VO2peak was related to a 5.31 cm³ (95% CI, 3.27 to 7.35 cm³) higher GM volume. Whole-brain voxel-based morphometry analyses revealed significant positive relations between CRF and local GM volumes. The VO2peak was strongly associated with GM volume of the left middle temporal gyrus (228 voxels), the right hippocampal gyrus (146 voxels), the left orbitofrontal cortex (348 voxels), and the bilateral cingulate cortex (68 and 43 voxels). Cardiorespiratory fitness was positively associated with GM volume, total brain volume, and specific GM and white matter clusters in brain areas not primarily involved in movement processing. These results, from a representative population sample, suggest that CRF might contribute to improved brain health and might, therefore, decelerate pathology-specific GM decrease.